SISTEM INFORMASI PENERAPAN E-CRM UNTUK MENINGKATKAN KUALITAS LAYANAN PELANGGAN DI FAMILY BOX PEKANBARU - Sri Astuti Handayani; Elvira Asril (J-Com (Journal of Computer), 2023)
Abstract:  Family Box is a karaoke entertainment venue located on Jl. HR Soebrantas Panam  Pekanbaru, during this pandemic the family box has experienced a decrease in customers so  that  the  family  box  needs  to  remanage  services  at  the  Family  box.  Family  Box  is  an  entertainment place that has a lot of competition with other karaoke places such as Koro-Koro,  Happy Puppy and so on. During this pandemic, the family box overcame the competition by  providing free 1 hour karaoke for customers who order 1 hour karaoke with the condition that  they follow and post the customer's personal Instagram or by ordering food that has been set  by the family box. And the family box also provides free Voucher Room for customers who order  food at karaoke with the condition that they order food which is also specified by the family  box. With this problem the researcher wants to build a family box management information  system in an effort to improve management in the family box. For this reason, the company  implements Electronic Customer Relationship Management (E-CRM) to best serve customers  so that customers feel satisfied and valued by the company. With CRM, companies will get  detailed information about customers. The information is in the form of customer personal data,  criticisms, suggestions and whatever is needed by the customer, so that the company can  provide responses, services and changes according to what the customer wants.  Keywords : information system; CRM; service; customer    Abstrak :Family Box adalah tempat hiburan karaoke yang terletak di Jl.HR Soebrantas Panam  Pekanbaru, dimasa pendemi ini family box mengalami penurunan pelanggan sehingga Family  Box perlu melakukan pengelolaan ulang terhadap pelayanan di Family Box. Family Box tempat  hiburan yang banyak memiliki persaingan dengan tempat karaoke lainnya seperti Koro-Koro,  Happy  Puppy  dan  lain  sebagainya.  Pada  masa  pendemi  ini   family  box  mengatasi  persaingannya dengan cara memberi free karaoke 1 jam bagi customer yang memesan 1 jam  karaoke dengan syarat mengikuti dan memposting instagram pribadi customer atau dengan  memesan makanan yang sudah ditetapkan Family Box. Dan Family Box juga memberikan Free  Voucher Room bagi customer yang memesan makanan pada saat karaoke dengan syarat  memesan makanan yang juga ditetapkan Family Box. Dengan permasalahan ini peneliti ingin  merancang dan membangun sebuah sistem informasi pengelolaan Family Box dalam upaya  peningkatan  pengelolaan  di  Family  Box.  Untuk  itu,  perusahaan  menerapkan  Electronic  Customer  Relationship  Management  (E-CRM)  untuk  melayani  pelanggan  dengan  sebaik- baiknya  agar  pelanggan  merasa  puas  dan  dihargai  oleh  perusahaan.  Dengan  CRM,  perusahaan akan mendapatkan informasi yang rinci mengenai pelanggan. Informasi itu berupa  data pribadi pelanggan, kritik, saran dan apa saja yang dibutuhkan oleh pelanggan, sehingga  perusahaan dapat memberikan tanggapan, pelayanan, serta perubahan-perubahan yang sesuai  dengan apa yang diinginkan pelanggan.  Kata kunci : sistem informasi; CRM; pelayanan; customer